A strategy for building and using a human reference pangenome [version 2; peer review: 2 approved] - Bastien Llamas; Giuseppe Narzisi; Valerie Schneider; Peter A. Audano; Evan Biederstedt; Lon Blauvelt; Peter Bradbury; Xian Chang; Chen-Shan Chin; Arkarachai Fungtammasan; Wayne E. Clarke; Alan Cleary; et al. (F1000Research, 2021)
In March 2019, 45 scientists and software engineers from around the world converged at the University of California, Santa Cruz for the first pangenomics codeathon. The purpose of the meeting was to propose technical specifications and standards for a usable human pangenome as well as to build relevant tools for genome graph infrastructures. During the meeting, the group held several intense and productive discussions covering a diverse set of topics, including advantages of graph genomes over a linear reference representation, design of new methods that can leverage graph-based data structures, and novel visualization and annotation approaches for pangenomes. Additionally, the participants self-organized themselves into teams that worked intensely over a three-day period to build a set of pipelines and tools for specific pangenomic applications. A summary of the questions raised and the tools developed are reported in this manuscript.